The Change in pH on Lactobacillus acidophillus Medium Containing D-fructose - Widia Pangetika; Ahmad Ni'matullah Al-Baarri; Anang Mohamad Legowo (Journal of Applied Food Technology, 2018)
This study aims to analyse the pH value on Lactobacillus acidophilus medium containing 3% (w/v) D-fructose. L. acidophilus was incubated at 37°C using MRS agar medium. Changes in pH values were measured for 48 hours. The non-sugar addition was also used as a comparison. Based on this research it could be seen that D-fructose slightly decreased pH in the medium at 48 hour incubation. This research might be useful to provide information on the potential use of D-fructose as a medium to maintain the reduction in pH.